20th YEARS MONICA PROJECT IN NOVI SAD - INFLUENCE OF SOCIOPOLITICAL AND ECONOMIC CIRCUMSTANCES ON STROKE EPIDEMIOLOGY - Žikić, Milorad T (PONS - medicinski časopis, 2025)
Objective. To measure trends in CVD, acute myocardial infarction (AMI), and MU morbidity and mortality, assessing the extent to which these trends are associated with changes in known risk factors (RF), daily lifestyle habits, health care, and major socioeconomic characteristics. Measurements were carried out at the same time in defined communities in different countries on several inhabited continents. Methods MONICA combined the old with the new, routine standardized measurements of epidemiological parameter’s, RF and medical care were combined with quality control and publication of results on the internet, hypothesis testing and publication of study results in prestigious scientific journals. The hypothesis couldn’t be tested only on one population and without cooperation with the WHO, and the main activities were recording the incidence of AMI and stroke, coronary care, analysis of population samples and implementation of the intervention program. Incidence, morbidity, lethality and mortality of stroke, sociopolitical and economic characteristics, as well as stroke RF in the area of Novi Sad were investigated from 1979-1983-2002. in order to establish and implement the aforementioned protocols. Results The levels and distribution of the main RF that determined the undertaking of preventive activities and the implementation of intervention programs to protect residents from CVD are presented. The results of the MONICA project in Novi Sad were achieved by reducing the epidemiological indicators of stroke in a period of favorable social, political and economic conditions, and by worsening them in the opposite circumstances in all expressed aspects of people's lives and state functioning. Conclusion The hypothesis has been proven that the social community achieves a successful final mission of reducing stroke rates of morbidity and mortality by undertaking prophylactic measures, so that despite the development of reperfusion therapies for patients with acute ischemic stroke, prevention remains the approach of choice for reducing the its risk.
Keywords: MONICA project; cardiovascular diseases; stroke; risk factors; prevention; epidemiology